2005
DOI: 10.1021/jf048051t
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Steryl Ferulate Extracts from Rye and Wheat Bran

Abstract: Antioxidant activity of steryl ferulates from other sources than rice have not yet been studied much, despite the fact that rice steryl ferulates (gamma-oryzanol) have been shown to possess good antioxidant activity. In this study, steryl ferulate extracts from wheat or rye bran were studied for their capability to inhibit hydroperoxide formation in bulk methyl linoleate and methyl linoleate emulsion. Further, their activity to scavenge DPPH radicals was analyzed. The activities were compared to synthetic ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 28 publications
2
74
0
1
Order By: Relevance
“…Presence of minor components of steryl ferulates in wheat germ oil (48 mg/100 g) observed in the study was also reported by Yongzhi and Wang (2005). Presence of ferulic acid moiety in steryl ferulates, a powerful antioxidant, whose esterified form (ferulates) is observed to be more active than the free form (ferulic acid) in liposomes (Nystrom et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Presence of minor components of steryl ferulates in wheat germ oil (48 mg/100 g) observed in the study was also reported by Yongzhi and Wang (2005). Presence of ferulic acid moiety in steryl ferulates, a powerful antioxidant, whose esterified form (ferulates) is observed to be more active than the free form (ferulic acid) in liposomes (Nystrom et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…CD contents of all oils increased slowly in the beginning of storage and the increase became faster thereafter. Moreover, the rate of formation of conjugated dienes and polymers reach an equilibrium, leading nonsignificant change in K232 (Nystrom et al, 2005). So, there was no significantly different between SBO and oil blends before 4th day; while, K232 values in SBO increased significantly.…”
Section: Oxidative Stabilitymentioning
confidence: 88%
“…Therefore, it seems reasonable to assume that γ-ORZ components could also be used for pharmaceutical purposes. Antioxidant activity of steryl ferulates (γ-ORZ) has been shown to be similar to that of non-esterified FA, indicating that the FA moiety is responsible for the antioxidant properties (20). The aim of this study was to investigate the structure-activity relationships of FA and sterol moieties of phytosteryl ferulates in relation to antioxidant and NF-κB activities in a cell-free system and living cultured cells.…”
Section: Introductionmentioning
confidence: 99%